Effectiveness of Health Education Reflective Methods Against Levels of Knowledge About the Dangers of Drugs in Students - Amirullah; Andi Nurlaela Amin (Comprehensive Health Care, 2022)
The background of the study is that Health Education with reflective methods allows the participants to have a dialogue in their minds and create listeners as well as personal stories to support themselves. The purpose of this study was to identify the effectiveness of health education reflective methods on the level of knowledge about the dangers of drugs in students in Madrasah Aliyah Guppi Batuara Gantarang District Bulukumba Regency. The method used is a quasi-experimental type pre-test-post-test non-randomized control group design. The sample in the study was X-class students consisting of 30 intervention group respondents and 30 control group respondents. The results of the Uji statistic using the Wilcoxon test, namely the intervention group using reflective methods obtained a value of p: 0.000 which means that there is a change between the level of knowledge before and after being given the reflective method and the control group before and after being given counseling there is no change in the level of knowledge with the value of P 0. 231 means that there is no change between the control groups before and after counseling. Conclusions and suggestions that health education with reflective methods are more effectively used in the level of knowledge of students about the dangers of drugs in Madrasah Aliyah Guppi Batuara Gantarang District Bulukumba Regency. It is hoped that reflective health education methods can be applied routinely to students or adolescents to avoid drug use.